Toward Data-Driven Collaborative Dialogue Systems: The JILDA Dataset - Irene Sucameli; Alessandro Lenci; Bernardo Magnini; Manuela Speranza; Maria Simi (IJCoL)
Today’s goal-oriented dialogue systems are designed to operate in restricted domains and with the implicit assumption that the user goals fit the domain ontology of the system. Under these assumptions dialogues exhibit only limited collaborative phenomena. However, this is not necessarily true in more complex scenarios, where user and system need to collaborate to align their knowledge of the domain in order to improve the conversation and achieve their goals.To foster research on data-driven collaborative dialogues, in this paper we present JILDA, a fully annotated dataset of chat-based, mixed-initiative Italian dialogues related to the job-offer domain. As far as we know, JILDA is the first dialogic corpus completely annotated in this domain. The analysis realised on top of the semantic annotations clearly shows the naturalness and greater complexity of JILDA’s dialogues. In fact, the new dataset offers a large number of examples of pragmatic phenomena, such as proactivity (i.e., providing information not explicitly requested) and grounding, which are rarely investigated in AI conversational agents based on neural architectures. In conclusion, the annotated JILDA corpus, given its innovative characteristics, represents a new challenge for conversational agents and an important resource for tackling more complex scenarios, thus advancing the state of the art in this field.